REPRESENTASI VISUAL DAN VERBAL BUDAYA INDONESIA DALAM MODUL AJAR ELEKTRONIK BIPA BERBASIS WISATA: KAJIAN SEMIOTIKA PIERCE - Muhafid Ayub Indhitaftiyan; Dian Uswatun Hasanah (2025)
An understanding of the language and culture is important for foreign speakers to be able to interact and value Indonesian cultural diversity. Currently, technology can be used to facilitate foreign supporters in the learning process. However, often teaching modules are lacking in conveying cultural wealth both visually and verbally, likewise with the use of technology. The use of BIPA's teaching modules is charged with Indonesian culture will be more effective in helping foreign speakers to learn and appreciate the diversity of Indonesian culture. Therefore, this study aims to identify Indonesian visual and verbal interpretations in the BIPA Tourism-Based Electronic Modules BIPA Tourism. This module selection is based on the importance of introducing Indonesian culture through a tourism sector that often attracts the attention of rich foreign speakers rich in cultural traditions. The method used in this study is descriptive qualitative. The analytical technique used is with a semiotic approach from Charles Sanders Pierce. Data sources use BIPA Electronic Modules Tourism Based. Meanwhile, the data is visual and verbal in the teaching module. The data is collected by the recording technique with the validity of the data used is triangulation of the theory. The results of the analysis show that the depiction of Indonesian culture in this module is very dependent on icon signs such as images of the Borobudur Temple and typical food and symbols like vocabulary related to the values of tradition or diversity concepts. Apart from icons and symbols, there is also an index giving concrete point to Indonesian cultural diversity. Digitalization in this Teaching Module is realized in the form of E-Book that can be accessed via the internet. The results of this study indicate that the crucial role of BIPA teaching modules in building cultural understanding, as well as the relevance to adapt information in the digital era.